Efficacy of Sunitinib in Elderly Patients with Metastatic Renal Cell Carcinoma: Data from Real-World Clinical Practice - Poprach, Alexandr; Lakomy, Radek; Bortlicek, Zbynek; Melichar, Bohuslav; Pavlik, Tomas; Slaby, Ondrej; Vyzula, Rostislav; Svoboda, Marek; Kiss, Igor; Studentova, Hana; Zemanova, Milada; Fiala, Ondrej; et al. (Drugs & aging, 2016)
BACKGROUND: Although a significant proportion of patients with metastatic renal cell carcinoma (mRCC) are elderly, the data on the outcomes of targeted therapies in this population are limited. The aim of the present retrospective registry-based study was to analyse efficacy and toxicity of sunitinib as the first-line targeted therapy of elderly mRCC patients. PATIENTS AND METHODS: The national RENal information system registry of mRCC patients treated with targeted agents in the Czech Republic was used as the data source. Of the 1315 patients treated with sunitinib as first-line targeted therapy, 1016 and 299 patients were aged <70 and ≥70 years, respectively. RESULTS: Elderly patients had a significantly longer interval from diagnosis to the initiation of therapy. Median progression-free survival was 10.8 months (95 % confidence interval 9.8-11.8) and 8.8 months (7.2-10.4) for patients aged <70 and ≥70 years, respectively (p = 0.321). Median overall survival was 31.9 months (27.9-35.9) and 26.3 months (21.3-31.2), respectively (p = 0.044). Significantly more elderly patients started on a reduced dose of sunitinib or discontinued the treatment prior to progression because of adverse events. CONCLUSIONS: The differences in patient profile and dose-reduction rates point to a different approach in the management of older and younger patients in daily clinical practice. The lower dose intensity of sunitinib in the elderly population may have translated into inferior survival.
Keywords: Sunitinib; nádory ledvin; Disease-Free Survival; Neoplasm Metastasis; Pyrroles; retrospektivní studie; protinádorové látky; progrese nemoci; karcinom z renálních buněk; indoly; Česká republika; vztah mezi dávkou a účinkem léčiva; Kidney Neoplasms; Age Factors; Aged; senioři; Disease Progression; registrace; pyrroly; sunitinib; Czech Republic; lidé; Humans; Indoles; věkové faktory; Carcinoma, Renal Cell; Registries; Retrospective Studies; čas zasáhnout při rozvinutí nemoci; metastázy nádorů; Dose-Response Relationship, Drug; přežití bez známek nemoci; Antineoplastic Agents; Time-to-Treatment